How to prevent fracture of NiTi files - Živković Slavoljub; Popović-Bajić Marijana; Jovanović-Medojević Milica; Nešković Jelena (Serbian Medical Society - Dental Section, Belgrade, 2021)
More certain therapeutic and significantly facilitated solution of everyday endodontic problems are provided by the introduction of NiTi rotary files in endodontic practice and their proper application. However, their widespread use has caused more and more frequent fractures and has become a significant frustrating factor that diminishes their numerous benefits. Torsional stress and cyclic fatigue are the main reasons for the occurrence of a fracture, and the frequency of NiTi file fractures is exactly proportional to the degree of bending of the canal, knowledge of the features of the file, ie. the skill and expertise of the therapist. The most dominant factor for the occurrence of fractures is the dentist who, in addition to manual dexterity, must have a good knowledge of the anatomy of various canal systems and file design in order to make the best choice for each individual case. Properly formed access cavity and knowledge of the working part of NiTi files enable maximum realization of endodontic skills, increased efficiency of intervention and reduced possibility of error during canal instrumentation. The special treatment of NiTi alloy and new solutions related to the design of the working part have significantly increased file flexibility and resistance to cyclic fatigue. Specific design (reduced number of threads, change of conicity, interruption of blade continuity), reduced engagement of file, ie. change of dynamics of movement in the canal (full rotation, reciprocal, eccentric, transaxial), as well as reduced number of processing files, have also significantly influenced the reduction of fracture risks. The aim of this paper was to analyze the most common reasons for the fracture of NiTi files and emphasize measures and factors that can increase their safe use and reduce complications during canal instrumentation.